BUDAYA KOMUNIKASI DALAM MENINGKATKAN PARTISIPASI POLITIK PEREMPUAN. (Analisis partisipasi politik Perempuan di partai politik) - Nurhakki Nurhakki (KOMUNIDA : Media Komunikasi dan Dakwah, 2015)
Culture is a form of communication habits of interaction that is built up in society. Patriarchal hegemony affects the dominant form of interaction and sub-dominant between male and female, have an impact on the lives of women reached the level of communication behavior. As a result, women in political roles at several barriers faced among others, the domestication of women who gave birth to a more intense interaction model is built on communal group (ingroup) and will be faced with the threat of cultural shock (culture shock) when dealing with multicultural culture outgroup political area is the domain of men. Women become silent (silent) due to frustrated communication (Communication frustated) because the behavior of ethnocentrism, and experience the tension (anxiety) in communication. Stereotypes also one of the factors inhibiting women because of the quality of the universal generalized to the ability that is identical with the domestic. As a result, women do not occupy a strategic position of decision makers, and not involved in the process and results of political decisions that are less accommodating toward women. Political culture is still very strong with masculinity tend to use harsh methods and the most votes, and put men in decision-making, with the pattern of political rights of women administrators neglected, on the other hand women do not have the courage to be critical of the treatment these discriminatory. Yet culture is the result of the human mind open to change. If the problem of low female roles result from cultural communication although the approaches and strategies carried out with such communication approaches, capacity building of women by building an extensive interaction within the community, improve self-concept in a positive direction, and approach to parenting in the family.